Deciphering Aspergillus section Terrei in Galleria mellonella model: a clade-specific pathogenicity characterization - Roya Vahedi-Shahandashti; Jos Houbraken; Vit Hubka; Martin Meijer; Bettina Gudrun Zelger; Ulrike Binder; Cornelia Lass-Flörl (Microbiology Spectrum)
ABSTRACT The Aspergillus genus encompasses a diverse array of species, some of which are opportunistic pathogens. Traditionally, human aspergillosis has primarily been linked to a few Aspergillus species, predominantly A. fumigatus. Changes in epidemiology and advancements in molecular techniques have brought attention to less common and previously unrecognized pathogenic cryptic species. Despite the taxonomic recognition of many cryptic species in section Terrei, their virulence potential and clinical implications, compared to A. terreus sensu stricto, remain poorly understood. Hence, the current study utilized the alternative in vivo model Galleria mellonella to evaluate the virulence potential of 19 accepted Aspergillus species in section Terrei, classified into three series (major phylogenetic clades): Terrei, Nivei, and Ambigui. Analyzing the median survival rates of infected larvae of all species in each series revealed that series Ambigui has a significantly lower virulence compared to series Terrei and Nivei. Taking a closer look at series Terrei and Nivei revealed a trend of survival within each clade, dividing the species into two groups: highly virulent (up to 72 h survival) and less virulent (up to 144 h survival). Histological observation, considering fungal distribution and filamentation, further supported this assessment, revealing increased distribution and hyphal formation in virulent species. Additionally, the susceptibility profile of conventional antifungals was determined, revealing an increased azole minimum inhibitory concentration for some tested cryptic species such as A. niveus and A. iranicus. Our results highlight the importance of cryptic species identification, as they can exhibit different levels of virulence and show reduced antifungal susceptibility.IMPORTANCEWith changing fungal epidemiology and an increasingly vulnerable population, cryptic Aspergillus species are emerging as human pathogens. Their diversity and clinical relevance remain underexplored, with some species showing reduced antifungal susceptibility and higher virulence, highlighting the need for better preparedness in clinical practice. Using the Galleria mellonella model, we assessed the virulence of Aspergillus species of section Terrei, including cryptic and non-cryptic species, across three series Terrei, Nivei, and Ambigui. The results revealed significant virulence variation among the series, with some cryptic species displaying high virulence. Histological analysis confirmed increased hyphal formation and fungal spread in the more virulent species. Additionally, elevated azole minimum inhibitory concentrations were also observed in certain cryptic species. This study presents novel insights into the pathogenicity of Aspergillus section Terrei, emphasizing the critical importance of accurately identifying cryptic species due to their diverse virulence potential and antifungal resistance, which may have substantial clinical implications.